Ganoderma lucidum polysaccharide inhibits UVB‐induced melanogenesis by antagonizing cAMP/PKA and ROS/MAPK signaling pathways. Issue 5 (26th October 2018) - Hu, Shuanghai; Huang, Jinhua; Pei, Shiyao; Ouyang, Yujie; Ding, Yufang; Jiang, Ling; Lu, Jianyun; Kang, Liyang; Huang, Lihua; Xiang, Hong; Xiao, Rong; Zeng, Qinghai; et al.
Abstract: Ultraviolet (UV)‐induced pigmentation is very common in clinical practice, but the current treatments are rarely effective, accompanied by some side effects. Ganoderma lucidum polysaccharide (GLP) is a natural antioxidant with no toxic side effects, which can antagonize UVB‐induced fibroblast photo aging. The study aims to explore the role of GLP in inhibiting UVB‐induced melanogenesis and its possible mechanism. The expression of melanogenesis genes such as microphthalmia‐associated transcription factor (MITF), tyrosine (TYR), tyrosinase related protein 1 (TYRP1), tyrosinase related protein 2 (TYRP2), ras‐related protein Rab‐27A (Rab27A), and Myosin shows an upward trend after exposure of B16F10 and PIG1 cells to UVB irradiation, but GLP can downregulate the expression of genes related to UVB‐induced melanogenesis. GLP can inhibit UVB‐activated protein kinase A (PKA) and mitogen‐activated protein kinase (MAPK) signaling pathways. Besides, GLP protects mitochondria from UVB damage and inhibits reactive oxygen species (ROS) production. Also, UVB‐induced cyclic adenosine monophosphate (cAMP) can be inhibited. It has been found in the experiments of UVB‐induced skin pigmentation in zebrafish that GLP is capable of inhibiting UVB‐induced skin pigmentation. Meanwhile, it can greatly relieve erythema reaction in guinea pig skin caused by high‐dosage UVB irradiation. In conclusion, this study shows that GLP can inhibit UVB‐induced melanogenesis by antagonizing cAMP/PKA and ROS/MAPK signaling pathways and is a potential natural safe whitening sunscreen additive. Abstract : This study is the first to explore the role of Ganoderma lucidum polysaccharide (GLP) in inhibiting Ultraviolet B (UVB)‐induced melanogenesis and its possible mechanism. we found that GLP could inhibit UVB‐induced melanogenesis by antagonizing cyclic adenosine monophosphate/protein kinase A (cAMP/PKA) and reactive oxygen species/mitogen‐activated protein kinase (ROS/MAPK) signaling pathways and is a potential natural safe whitening sunscreen additive